Effects of Nutrients Ca and K on Anaerobic Digestion of Food Waste - Firda Mahira Alfiata Chusna; Lukhi Mulia Sitophyta; Rachma Tia Evitasari (Universitas Ahmad Dahlan, 2022)
We often find food waste daily, especially on household and restaurant scales. Using food waste for helpful something, biogas is an alternative to reduce wasted waste and produce renewable energy. The anaerobic digestion process is a process that decomposes organic material into biogas with the help of microorganisms in conditions without oxygen. Adding nutrients in the anaerobic digestion process can positively affect biogas-producing microorganisms. One of the nutrients or nutrients studied this time is Ca and K. The provision of nutrient Ca has a positive effect, namely a significant increase in biogas production compared to without the addition of nutrients. However, adding K does not positively impact biogas production is inhibited. Excessive amounts of nutrient K can inhibit the process by inhibiting microorganisms in breaking down intermediate products into biogas. The largest volume of biogas produced for five days came from the reactor with the addition of nutrient Ca, which was 15072 cm3, while the control reactor and reactor with the addition of nutrient K produced biogas of 1648.5 cm3 and 15.7 cm3. The addition of nutrient Ca increases biogas production more than nine times.